INCLUSIVE EDUCATION IN THE CONTEXT OF REGIONAL AND LANGUAGE FEATURES: REAL EXPRESSION OF THE MULTI-VECTOR APPROACH IN KARAKALPAK SCHOOLS - Pirniyazova, G.N. (SCIENCE and SOCIETY, 2026)
This article analyzes the practical manifestation of inclusive education in educational institutions in Karakalpakstan. Taking into account territorial and linguistic factors, it deeply studies the essence, pedagogical mechanisms and practical possibilities of a multi-vector approach. Based on existing experience, an adapted educational model is proposed as a solution to social, linguistic and psycho-pedagogical problems.